Analysis of the electric conductivity and ph behaviors in recycled drainage solution of rose cv. charlotte plants grown in substrate (2013)
In open soilless cropping systems contamination from nutrientlixiviation is generated making it necessary to design closed orsemi-closed systems, which require the determination of themaximum saline levels in recycling solutions. In this study, theelectric conductivity (EC) and pH behaviors were analyzed indrainage solution intended for recycling in the crop; in addi-tion, parameters were used to estimate nutrient availability forthe plants in a substrate based cropping system. This researchproject was carried out under greenhouse conditions in the mu-nicipality of Mosquera (Colombia). Rose cv. Charlotte graftedon ‘Natal briar’ stocks were used, sown in pots arranged onelevated beds, 15 m in length. This project was carried out usinga split-plot design with sub-plots (with the substrate as the mainplot and the recycling as the sub-plot), three kinds of substrateand three recycling percentages (0, 50, and 100%), for a total of27 experimental units. Substrate mixtures based on burned ricehusk and coconut fiber were used. Recycling during one harvestcycle of the roses did not show EC and pH values above thosethat are considered to have a negative impact on production;however, an increasing behavior in the EC and pH values wasobserved. Likewise, no significant differences between the 50and 100% recycling were observed, which means 100% recyclingcan be used, optimizing nutrient use and water conservation.